Can Emerging Countries Mitigate the Effect of Original Sin Problem in Achieving External Debt Sustainability - Günes, Sevcan; Akin, Tuğba (Central European Journal of Economic Modelling and Econometrics, 2023)
Due to the spike in inflation, the implementation of easy monetary and fiscal policies since the pandemic appears to be coming to an end. The shift towards tighter policies raises concerns about debt sustainability in developing countries, particularly due to the challenge of the “original sin” problem. Given these premises, to analyze debt sustainability for emerging countries, this study focuses on foreign exchange revenue capability and employs external debt-creating (imports, reserves and interest payments) and reducing variables (exports, reserve return and net transfers) for 1995-2020. The results of this panel cointegration estimation for 15 EMDE countries are 0.74 and 0.70 for CCEMG and AMG estimators respectively which indicates moderate sustainability as whole sample countries. However, the individual estimators vary widely for each individual country from weak to strong sustainability.